Love You, Little Lady - Young, Brett, 1981-; O'Callaghan, Airin (Nashville : Thomas Nelson, 2021)
"From country music sensation Brett Young comes a heartwarming celebration of parental love and tenderness based on his touching song "Lady.""--
Keywords: Young, Brett, -- 1981- -- Juvenile literature; Fathers and daughters -- Juvenile literature; Mothers and daughters -- Juvenile literature